2010
DOI: 10.1111/j.1442-9071.2010.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Syphilitic retinitis and uveitis in HIV‐positive adults

Abstract: This case series reinforces the importance of considering syphilis in the differential diagnosis of many ocular presentations, but in particular retinitis. Retinitis appears to be the predominant presentation in HIV-infected individuals, suggesting that HIV infection may somehow modulate the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
3
40
0
Order By: Relevance
“…Tran et al [15] found 7 of 19 eyes (39%) in HIV-positive patients with posterior uveitis to have necrotizing retinitis. Some studies report a lower rate [6], whereas a recent series [18] reports 6 of 6 HIV positive patients with retinitis. It is striking that the majority of cases of syphilitic retinitis, and necrotizing retinitis in particular, are reported in HIV-positive patients [6,15,26,28,30] suggesting a more severe presentation of syphilitic uveitis in the HIV population [31].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Tran et al [15] found 7 of 19 eyes (39%) in HIV-positive patients with posterior uveitis to have necrotizing retinitis. Some studies report a lower rate [6], whereas a recent series [18] reports 6 of 6 HIV positive patients with retinitis. It is striking that the majority of cases of syphilitic retinitis, and necrotizing retinitis in particular, are reported in HIV-positive patients [6,15,26,28,30] suggesting a more severe presentation of syphilitic uveitis in the HIV population [31].…”
Section: Discussionmentioning
confidence: 91%
“…Though previously thought to be uncommon, recent studies [15,18] demonstrate increasing rates of syphilitic retinitis. Tran et al [15] found 7 of 19 eyes (39%) in HIV-positive patients with posterior uveitis to have necrotizing retinitis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Multifocal choroiditis is caused by many etiologies including sarcoidosis, VKH disease, sympathetic ophthalmia, histoplasmosis, birdshot chorioretinopathy, serpiginous choroidopathy, multiple white-dot syndromes and nematode-associated disease [44,[88][89][90]. A discussion of the whitedot syndromes is beyond the scope of this paper; however, the diagnoses are made based on clinical history, ocular examination, clinical course, characteristic findings on ocular imaging and in some cases electrophysiologic testing.…”
Section: Grillo Levinson and Gordonmentioning
confidence: 99%
“…[1], [2] , Sandra Dias [3] and Fabiana Gonzaga [1] [1]. Ocular complications are common in acquired immunodefi ciency syndrome (AIDS) and occur in 50-75% of patients throughout the course of their illness.…”
Section: Paulo Sérgio Ramos De Araujomentioning
confidence: 99%